On the solution of fuzzy dual linear systems of equation - Kiasari, S. M. Khorasani; Ramhormozi, L. Abdollahzadeh (International Journal of Applied Mathematical Research, 2015)
In this paper the exact, multiple and approximation solutions of Dual fuzzy linear systems of equations(DFLSE) with triangular variable are investigated based on a 1-level expansion. To this end, 1-level of DFLSE are solved for calculating the cores of fuzzy solution and then its spreads are obtained by solving an optimization problem with a special objective function. Finally, the existence of solution of DFLSE is proved in details and some numerical examples are solved to illustrate the accuracy and capability of the method